Preparation and Characterization of Reactive Type Dripping Agent Containing a-Double Bond - Li1, Wenfei; Yao2, Ruixiang; Lin1, Yang; Yao3, Zhanhai; Liu1, Shumei (Asian Journal of Chemistry, 2014)
A reactive type dripping agent containing a double bond, sorbitan monostearate-itaconic anhydride (Span60-IAH) was synthesized with sorbitan monostearate (Span60) and itaconic anhydride as main starting materials. The chemical structures of Span60-IAH were characterized by Fourier transform infrared (FT-IR) spectroscopy and 1H NMR. The effect of reaction time on conversion of Span60-IAH was studied. The surface activity and surface tension of Span60-IAH were evaluated by a drop weight method. Thermal stability of Span60-IAH and Span60 were investigated by TGA. When residual weight (%) was 90 %, the decomposition temperature of Span60-IAH was about 28 °C higher than that of Span60. The wettability is expressed by the water contact angle.